Behind the Green Door: Unpacking the Item Number and Its Ecology. (December 2018) - Mukherjee, Silpa
The term 'item numbers' emerged in film journalism sometime in the late 1990s as an industry slang. It later evolved into a heterogeneous cinematic language with its investment in production design, choreography, special effects and specialised editing. Using interviews with industry professionals, this article will unpack the production ecology of the hypersexualised and hybrid song and dance spectacle.